A Conceptual Typology of Kin‐State Mediation. Issue 3 (19th July 2016) - Kocadal, Özker
Abstract : In this article, I argue that kin states can play major roles in international mediation processes involving their kin communities. Although kin states may be naturally biased toward their kin, kin states are sometimes actively involved in mediation processes and such involvement is even encouraged by third‐party mediators. In this study, I divide the various roles assumed by kin states in mediation into four main conceptual categories: promoter, quasi‐mediator, powerbroker, and enforcer. My analysis presumes that a kin state can use its close ties with its kin community to make third‐party mediation more successful. I support and illustrate this model using cases of kin‐state involvement in peace processes and examine both the benefits and complications that kin‐state mediation can entail. This study contributes to scholarship examining the effectiveness of biased mediators. I conclude that the role a kin state assumes in a mediation is often context‐dependent, but that third‐party mediators and the international community can use their leverage over kin states to improve the peace process.